KETAHANAN NASIONAL BERBASIS KOKOHNYA KELUARGA INDONESIA MEMASUKI MASYARAKAT EKONOMI ASEAN (MEA) - Yudiyanto Yudiyanto (Ri'ayah: Jurnal Sosial dan Keagamaan, 2016)
Without knowing us, the Indonesian nation security has potential to debilitate when take part in ASEAN Economic Society (MEA). ASEAN expand market will make charity in flow of goods, services, and labors followed by cultural influence. Not only has the positive impact, ASEAN expanded market also give negative impact because of hedonist and materialist culture influence. Family is the first institution creating individuals as the candidate of society and nation. The strong family is capable both in creating and educating the next generation who has balancing in spiritual, intellectual, and emotional which can help them in MEA competition arena. Those excellent generations have important role in community and national endurance in the middle of regional rivalries ASEAN nations in MEA. The aim of this paper is to explain the important role of family in creating national endurance when take part in MEA, through qualitative conceptual paper method and using literature review.